WOMEN IN PRISION AND FUNDAMENTAL GUARANTEES FROM THE PERSPECTIVE OF THE DIGNITY OF THE HUMAN PERSON - Daiana Oliveira Silva, Laura (Revista Gênero e Interdisciplinaridade, 2022)
The present work proposes to investigate the women in brazilian penitenciaries, whose structure is not adapted. An analysis will be carried out in the perspective of the principle of human dignity, the fundamental rights, analyzing whether are implemented. It will be analyzed the appearance of penitentiaries during history and how started to be used as a form of punishment for crimes. It will address the concept of gender, the discrimination of women about society, and their insertion in the context of criminality. To this end, an exploration of legislation, doctrine, articles, and official data on female incarceration was carried out.